(untitled) (Agroindustrial Science, 2026)
Currently, agricultural production systems face global problems such as adaptation to climate change and habitat loss. The intensive agriculture approach, product of linear economy, has generated traditional systems to be left aside. Despite this, the milpa system is still essential for food safety and the basis of local economy; throughout its history strategies and innovations have been incorporated to optimize available resources, where traditional knowledge has been the basis of resiliency of this system; however, knowledge continues to be incorporated, although at a slower rate. For this reason, systematic review has been carried out of the main strategies that are used by actors and institutions related to the milpa system in Mexico, with the aim of presenting a harmonic vision under the framework of contributions of sustainability and the circular economy , the results allow conceptualization of the milpa system as an adaptable entity potential for improvement and not static, as well as agroecological space where the adequate management of bioproducts and waste converge.